2016
DOI: 10.3201/eid2211.160914
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to Invasive Group BStreptococcusDisease in Adults

Abstract: Antibodies to capsular polysaccharides and pilus proteins develop in recovering adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Group B streptococcus is also recognized as an important health threat in immunocompromised adults, i.e., the elderly and patients with diabetes mellitus or HIV infections. Notably, the most common manifestations are skin/soft tissue infections and bacteremia ( 127 129 ), indicating that in these patients barrier immunity is important for the normal containment of GBS, similar to the situation in infants. The immaturity of the neonatal immune system in comparison to that of the adult was reviewed in detail elsewhere ( 130 132 ) and we will therefore focus on selected GBS-related aspects.…”
Section: Cellular Innate Immunity and Resistance To Gbsmentioning
confidence: 95%
“…Group B streptococcus is also recognized as an important health threat in immunocompromised adults, i.e., the elderly and patients with diabetes mellitus or HIV infections. Notably, the most common manifestations are skin/soft tissue infections and bacteremia ( 127 129 ), indicating that in these patients barrier immunity is important for the normal containment of GBS, similar to the situation in infants. The immaturity of the neonatal immune system in comparison to that of the adult was reviewed in detail elsewhere ( 130 132 ) and we will therefore focus on selected GBS-related aspects.…”
Section: Cellular Innate Immunity and Resistance To Gbsmentioning
confidence: 95%
“…To our knowledge, studies on the seroprevalence against GBS CPS in various age groups have not been performed worldwide. Baker et al 31 and Edwards et al 32 reported opsonophagocytic antibodies against type III or V during the third trimester of pregnant women, while the DEVANI program described the prevalence of antibodies against CPS for Ia, Ib, and III serotypes in pregnant women. 10 In non-pregnant adults, Edwards et al 32 reported a CPS-specific IgG response after invasive GBS infection in acute and convalescent-phase serum.…”
Section: Discussionmentioning
confidence: 99%
“…Baker et al 31 and Edwards et al 32 reported opsonophagocytic antibodies against type III or V during the third trimester of pregnant women, while the DEVANI program described the prevalence of antibodies against CPS for Ia, Ib, and III serotypes in pregnant women. 10 In non-pregnant adults, Edwards et al 32 reported a CPS-specific IgG response after invasive GBS infection in acute and convalescent-phase serum. However, as described, their study did not evaluate the functional aspect of immune responses, which is a critical limitation for the study in adults and the elderly populations.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between MLST typing and drug resistance 63 positive GBS isolates through double disk Vancomycin has a potential damage to animal embryos. GBS vaccines against non-pregnant adults can effectively prevent bacteremia, however, such research has not been applied to clinical treatment in China[37]. Besides, as is known to all, China is a developing country with large population base.…”
mentioning
confidence: 99%